Diversity of fish species in the Tekam and Salan Rivers, Jerantut Pahang / Mohd Shahrul Azli Ab Rajab - Ab Rajab, Mohd Shahrul Azli (Faculty of Applied Sciences, 2017)
Sampling on the diversity of fish fauna were conducted in Tekam and Salan rivers, Jerantut Pahang. Fish were sampled from six stations from three different zones of the rivers, namely the upper site, middle site, and lower site. A total of 16 fish species belonging to seven families were recorded. Analyses based on the number of individuals caught showed that 80% of total catch was represented by the Cyprinids. Labiobarbus leptocheilus, Cyclocheilichthys heteronema, and Puntius marginatus were the most distributed occurring within Tekam river being present in the upper, middle, and lower site of the river, while Hemibagrus nemurus, Pristolepis fasciatus, Puntius schwanenfeldii, and Rasbora lateristriata were the most distributed within the Salan river occuring in all the zone sites. Overall, fish species diversity, species richness and evenness were higher at Tekam river compared to Salan river, although occurrences was significantly more abundant in Salan river. The causes of the differences could be due to hydrographic conditions such as temperature, pH and dissolve oxygen. In both rivers, temperature recorded ranged from 25°C - 26.9 ° in both. Water pH value varies between 6.52 to 6.97 and dissolved oxygen ranges from 4.93 mg/l to 6.83 mg/l. Thus, river physical and biological factors influence the occurrence, distribution, abundance and diversity of river tropical fishes.